Ionic Liquid Aqueous Two-Phase Systems From a Pharmaceutical Perspective - McQueen, Lisa; Lai, David (Frontiers in Chemistry, 2019)
Abstract Aqueous Two-Phase Systems (ATPSs) have been extensively studied for their ability to simultaneously separate and purify active pharmaceutical ingredients (APIs) and key intermediates with high yields and high purity. Depending on the ATPS composition, it can be adapted for the separation and purification of cells, nucleic acids, proteins, antibodies, and small molecules. This method has been shown to be scalable, allowing it to be used in the milliliter scale for early drug development to thousands of liters in manufacture for commercial supply. The benefits of ATPS in pharmaceutical separations is increasingly being recognized and investigated by larger pharmaceutical companies. ATPSs use identical instrumentation and similar methodology, therefore a change from traditional methods has a theoretical low barrier of adoption. The costs of typical components used to form ATPS at large scale, particularly that of polymer-polymer systems, is the primary challenge to widespread use across industry. However, there are a few polymer-salt examples where the increase in yield at commercial scale justifies the costs of using ATPSs for macromolecule purification. More recently, Ionic Liquids (ILs) have been used for ATPS separations that is more sustainable as a solvent, and more economical than polymers often used in ATPSs for small molecule applications. Such IL-ATPSs still retain much of the attractive characteristics such as customizable chemical and physical properties, stability, safety, and most importantly, can provide higher yield separations of organic compounds, and efficient solvent recycling to lower financial and environmental costs of large scale manufacturing.